Ultimate response and design of stainless steel continuous beams. (13th September 2017) - Kokosis, Georgios; Gkantou, Michaela; Theofanous, Marios; Dirar, Samir
ABSTRACT: Due to lack of available experimental data, plastic design of stainless steel (SS) indeterminate structures is currently not permitted by Eurocode 3: Part 1.4, despite the excellent material ductility and the existence of a Class 1 slenderness limit, thereby compromising design efficiency. The high initial material cost warrants the development of novel design procedures, in line with the observed structural response, which fully utilise its merits, improve cost‐effectiveness and minimise material consumption. This paper focuses on the response and design of stainless steel continuous beams. FE models of austenitic and lean duplex stainless steel SHS and RHS were developed and validated against published test data. The validated FE models were used to conduct parametric studies, in order to obtain structural performance data over a range of cross‐sectional slendernesses, cross section aspect ratios, moment gradients and loading arrangements. Based on obtained results, it was concluded that the current Eurocode 3: Part 1.4 approach significantly underestimates the strength of continuous beams. This is because the formation of successive plastic hinges and moment redistribution in indeterminate structures with adequate deformation capacity, as well as the effect of strain‐hardening at cross‐sectional level, are not accounted for. It is shown that accounting for both strain‐hardening and moment redistribution is of paramount importance for design. To this end, the application of the Continuous Strength Method (CSM), which rationally accounts for local buckling at cross‐section level, is extended to the design of stainless steel indeterminate structures. Further research is underway to quantify the effect of high shear stresses on the design procedure and to extend the method to the design of pinned based and fixed based stainless steel frames.